Ambiguity, Role Conflict Towards Independence Commitment With Competence Mediation And Religiosity Moderation - Agus Bandiyono; M. Bilal Al Ashri (Jurnal Akuntansi, 2022)
This study aims to determine role ambiguity and role conflict on independence commitment with internal auditor competence as a mediating variable and the level of religiosity as a moderating variable. The population in this study were all employees of the Directorate General of Taxes throughout Indonesia. The sample in this study is the head of the internal control section and the directors of the Directorate General of Taxes. The questionnaires returned in this study amounted to 123 research samples. The results of this study indicate that role ambiguity and role conflict have a significant negative effect on the independence commitment of DGT UKI officers. The mediating variable of competence level of internal auditors cannot increase the commitment to independence. The moderator variable of religiosity level cannot have a significant impact on independence commitment.